Conservative treatment of postpneumonic thoracic empyema in children - Ozel, SK; Kazez, A; Kilic, M; Koseogullari, AA; Yilmaz, E; Aygun, AD (Springer, 2004)
Purpose. Many treatment modalities have been described for thoracic empyema in children but the optimal timing of appropriate treatment remains controversial. The aim of this study is to find out the outcome of postpneumonic empyema in children after a conservative approach. Methods. The reports of patients who were admitted to our hospital from January 1990 to October 2002 with a diagnosis of postpneumonic thoracic empyema were reviewed retrospectively. The comparative data were age, duration of prehospital illness, complaints, blood and pleural fluid analyses, radiological evaluations, microbiological studies, modes of treatment, duration of chest tube drainage, and length of hospital stay. Results. A total of 115 patients (65 males and 50 females), aged from 3 months to 13 years, were evaluated. The most common symptoms were fever (96.5%), cough (85.2%), and dyspnea (50.4%). Chest X-rays revealed a minimal collection in 22 (19.2%), a moderate collection in 40 (34.8%), and a massive collection in 53 patients (46%). Staphylococcus aureus was the most common microorganism isolated from the bacterial cultures and Mycobacterium tuberculosis was the next most common. Twelve patients (10.4%) underwent surgical decortication. The mean duration of chest drainage was 10.1 +/- 1.39 days. The mean hospitalization period was 24.2 +/- 6.15 days and it was significantly shorter in patients with a minimal collection than in those with a massive collection (13.9 +/- 2.21 vs 28.47 +/- 6.38 days, P < 0.01). Conclusions. The majority of postpneumonic thoracic empyema cases in children can be successfully treated with a conservative approach. Detailed investigations should also be done to rule out tuberculosis in these patients.
Keywords: thoracic empyema; postpneumonic; children; conservative treatment